Web based 3D terrain visualization using game engine - Che Mat, Ruzinoor; Mohamed Shariff, Abdul Rashid; Zulkifli, Abdul Nasir; Mohd Rahim, Mohd Shafry; Mahayudin, Mohd Hafiz (2015)
Recently, most of the Geographic Information System (GIS) applications now are moving toward into 3D environment where some of geo-browsers such as Google Map and Microsoft Virtual Earth are ready with this capability.Terrain visualization is the main part of these system.The aim of this paper is to discuss on the development of online 3D terrain visualization using unity 3D game engine.The process involved with the data preparation of terrain data (DEM) which need to be converted into HDR (header) and FLT (float) format.The terrain data then is imported into unity 3D for generating 3D terrain data. These data were pre-overlaid with the images data.Both types of data is then export into web player format using unity 3D.The web based development were design and draft suite to the applications and publish into the web server.The users can interact with this system in 3D environment terrains with the capability of walk through, view from different angle, first and third person view, and overlaid mode view.It therefore gives benefits to potential visitors, decision makers and planners to explore and gain experience the 3D environment of terrains virtually.